COMMERCIAL CARCASS PIECES OF BROILER WHICH WERE GIVEN THE MAGGOTS LATTERS AS A REPLACEMENT OF COMMERCIAL RATIONS - N. L. A. K., Pratiwi; Astawa, I P. A.; Sudiastra, I W. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the effect of giving maggot caterpillars as a substitute for commercial rations on commercial broiler carcass pieces. This research was conducted for 8 weeks located in Nyitdah Village, Kediri District, Tabanan Regency, Bali and used a completely randomized design (CRD) with 4 treatments and 4 replications consisting of 64 broilers with homogeneous body weight. The four treatments were rations without giving maggot as a control (P0), rations with 5% maggot replacement (P1), rations with 10% maggot replacement (P2), rations with 15% maggot replacement (P3). The variables observed were carcass, breast, thigh, wing and back percentages. The results showed that the percentage of broiler carcasses and breasts with maggot maggot feeding of 5% (P1), 10% (P2), 15% (P3) was significantly different (P<0.05) higher than P0. The average percentage of broiler wings and backs that received maggot maggot caterpillars of 5% (P1), 10% (P2), 15% (P3) was not significantly different (P> 0.05) lower than P0 whereas the percentage of thighs showed no results. significantly different (P>0.05) higher than P0. Giving maggot caterpillars as a substitute for commercial rations can increase the percentage of carcass and commercial carcass pieces of the chest with the best level at 5%.